Pretreatment with magnesium sulfate attenuates white matter damage by preventing cell death of developing oligodendrocytes. Issue 4 (23rd January 2018) - Seyama, Takahiro; Kamei, Yoshimasa; Iriyama, Takayuki; Imada, Shinya; Ichinose, Mari; Toshimitsu, Masatake; Fujii, Tomoyuki; Asou, Hiroaki
Abstract: Aim: Antenatal maternal administration of magnesium sulfate (MgSO4 ) reduces cerebral palsy in preterm infants. However, it remains controversial as to whether it also reduces occurrence of white matter damage, or periventricular leukomalacia. We assessed the effect of MgSO4 against white matter damage induced by hypoxic‐ischemic insult using a neonatal rat model and culture of premyelinating oligodendrocytes (pre‐OL). Methods: Rat pups at postnatal day (P) 6 were administered either MgSO4 or vehicle intraperitoneally before hypoxic‐ischemic insult (unilateral ligation of the carotid artery followed by 6% oxygen for 1 h). The population of oligodendrocyte (OL) markers and CD‐68‐positive microglia at P11, and TdT‐mediated biotin‐16‐dUTP nick‐end labeling (TUNEL)‐positive cells at P8 were evaluated in pericallosal white matter. Primary cultures of mouse pre‐OL were subjected to oxygen glucose deprivation condition, and the lactate dehydrogenase release from culture cells was evaluated to assess cell viability. Results: Pretreatment with MgSO4 attenuated the loss of OL markers, such as myelin basic protein and Olig2, in ipsilateral pericallosal white matter and decreased the number of CD‐68‐positive microglia and TUNEL‐positive cells in vivo . Pretreatment with MgSO4 also inhibited lactate dehydrogenase release from pre‐OL induced by oxygen glucose deprivation in vitro . Conclusion: Pretreatment with MgSO4 attenuates white matter damage by preventing cell death of pre‐OL.